Inflammation and Metabolism in Cancer Cell—Mitochondria Key Player - Neagu, Monica; Constantin, Carolina; Popescu, Iulia Dana; Zipeto, Donato; Tzanakakis, George; Nikitovic, Dragana; Fenga, Concettina; Stratakis, Constantine A.; Spandidos, Demetrios A.; Tsatsakis, Aristidis M. (Frontiers in Oncology, 2019)
Cancer metabolism is an essential aspect of tumorigenesis, as cancer cells have increased energy requirements in comparison to normal cells. Thus, an enhanced metabolism is needed in order to accommodate tumor cells' accelerated biological functions, including increased proliferation, vigorous migration during metastasis, and adaptation to different tissues from the primary invasion site. In this context, the assessment of tumor cell metabolic pathways generates crucial data pertaining to the mechanisms through which tumor cells survive and grow in a milieu of host defense mechanisms. Indeed, various studies have demonstrated that the metabolic signature of tumors is heterogeneous. Furthermore, these metabolic changes induce the exacerbated production of several molecules, which result in alterations that aid an inflammatory milieu. The therapeutic armentarium for oncology should thus include metabolic and inflammation regulators. Our expanding knowledge of the metabolic behavior of tumor cells, whether from solid tumors or hematologic malignancies, may provide the basis for the development of tailor-made cancer therapies.